(untitled) (Bangladesh Journal of Zoology, 2017)
The effect of probiotics mixed with floating feed on the growth and production of tilapia Oreochromis niloticus over a period of 120 days was evaluated. Four treatments were T1 (super biotic probiotics), T2 (biozyme probiotics), T3 (zymetin probiotics) and T4 (control) with three replicates. Higher growth of tilapia was found in T3 (272.78 g) followed by T2 (242.56 g), T1 (222.76 g) and T4 (199.35 g). The highest gross yield (8.82 kg m-3) was achieved in T3 compared to T2 (7.78 kg m-3), T1 (7.23 kg m-3) and T4 (6.35 kg m-3), which is manifolds higher than the earthen pond yield of tilapia in Bangladesh. The highest net profit (TK. 401.0 m-3) was obtained in T3 and the lowest (TK. 119.0 m-3) was in control (T4). Results suggest that probiotics can be used in feed to increase fish production. Bangladesh J. Zool. 45(1): 27-36, 2017